Gestão de riscos ocupacionais nos processos de secagem e armazenagem de grãos - Kunh, Peterson Diego (2023)
This research aims to develop and apply a model to perform occupational risk management during the grain storage and drying process, with which it is possible to characterize, prioritize, and propose measures that assist in resolving identified non-conformities. The model was applied in a unit located in the western region of Paraná and validated with professionals from the Specialized Service in Safety and Occupational Medicine, as well as a company that provides services in the area of occupational safety in the region. The research was divided into two articles, the first of which aims to carry out a practical approach to the model applied to the inspection of lightning protection systems using uncrewed aerial vehicles in the visual inspection activities of these systems, so that it is possible to carry out the planning of maintenance and activities carried out at height. This procedure allowed planning and directing maintenance work only where necessary. Among the main advantages is eliminating exposure to work carried out at height and greater agility and recording through photos and videos. Disadvantages include the dependence on weather conditions (no rain and strong winds), obstacles and cables used to support the structure, which makes it difficult to operate the equipment. The evaluation model can be improved by using the autonomous inspection of the system, which, combined with image and video analysis software, can identify non conformities. The second article aimed to identify, evaluate, prioritize and establish control measures of the exposure to heat and noise in the activities carried out, which generated a score that represents the situation of risks in the environment. Of the 104 possible points in the evaluation, occupational exposure to heat obtained the lowest score, 70 (normal level), which indicates good condition with restriction to the standard; for noise, the score obtained was 90 (normal level), in good condition, with few restrictions to the standard. With the model, it was possible to evaluate the risks, prioritizing, through the score generated, those of more critical levels (heat) in order to propose measures to assist the resolution (install a temperature and humidity meter in the environment and change the protective glove against thermal agents). Its application creates a database that will help identify and predict risk situations